Peranan kesepian sebagai moderator antara distres psikologis dengan kesejahteraan psikologis mahasiswa selama pandemi COVID-19: The role of loneliness as a moderator between psychological distress and the psychological well-being of students during the COVID-19 pandemic - Nurdiyanto, F A; Harjanti, Enggar Putri; Laban, Rinekso Wismanto (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2022)
The COVID-19 pandemic threatens students' psychological well-being. Distress and loneliness are prevalent psychological problems related to mobility restriction and